Increased Risk for Non-Melanoma Skin Cancer in Patients with Inflammatory Bowel Disease - Long, Millie D (2010)
BACKGROUND & AIMS: Patients with inflammatory bowel disease (IBD) might be at increased risk for certain malignancies. We evaluated the risk of non-melanoma skin cancer (NMSC) in patients with IBD and determined how immunosuppressive and biologic medications affect this risk. METHODS: We performed retrospective cohort and nested case-control studies using administrative data from PharMetrics Patient Centric Database. In the cohort study, 26403 patients with Crohn’s disease (CD) and 26974 patients with ulcerative colitis (UC) were each matched to 3 non-IBD controls. NMSC risk was evaluated by incidence rate ratio. In the nested case-control study, 387 CD patients and 355 UC patients with NMSC were each matched to 4 IBD patients without NMSC using incidence density sampling. Conditional logistic regression was used to determine the association between specific IBD medication use and NMSC. RESULTS: In the cohort study, the incidence of NMSC was higher among patients with IBD compared to controls (incidence rate ratio [IRR] 1.64, 95% confidence interval [CI] 1.51–1.78). In the nested-case control study, recent thiopurine use (≤90 days) was associated with NMSC (adjusted odds ratio [OR] 3.56, 95% CI 2.81–4.50), as was recent biologic use among patients with CD (adjusted OR 2.07, 95% CI 1.28–3.33). Persistent thiopurine use (>365 days) was associated with NMSC (adjusted OR 4.27, 95% CI 3.08–5.92), as was persistent biologic use among patients with CD (adjusted OR 2.18 95% CI 1.07–4.46). CONCLUSIONS: Patients with IBD, especially those that receive thiopurines, are at risk for NMSC. Appropriate counseling and monitoring of such patients with IBD is recommended.